2019
DOI: 10.3389/fnmol.2019.00202
|View full text |Cite|
|
Sign up to set email alerts
|

NEK7 Regulates NLRP3 Inflammasome Activation and Neuroinflammation Post-traumatic Brain Injury

Abstract: As one of the most common causes of mortality and disability, traumatic brain injury (TBI) is a huge psychological and economic burden to patients, families, and societies worldwide. Neuroinflammation reduction may be a favorable option to alleviate secondary brain injuries and ameliorate the outcome of TBI. The nucleotide-binding oligomerization domain, leucine-rich repeat and pyrin domain-containing 3 (NLRP3) inflammasome, has been shown to be involved in TBI. NIMA-related kinase 7 (NEK7) has been verified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 52 publications
0
44
0
Order By: Relevance
“…There has been increasing attention on the molecular mechanisms of NLRP3 in a number of diseases. Recent studies have reported significant protective effects resulting from suppression of NLRP3 inflammasome activation in liver fibrosis, systemic sclerosis, systemic lupus erythematosus, systemic sclerosis, diabetes, inflammasome-related eye disease, inflammatory bowel disease, rheumatoid arthritis, and CNS diseases (Zhou et al, 2016;Alegre et al, 2017;Rovira-Llopis et al, 2018;Shen et al, 2018;Yerramothu et al, 2018;Chen et al, 2019a). Meng et al (2019) demonstrated that PPARγ activation exerts an anti-inflammatory effect by suppressing NLRP3 inflammasome activation in spinal cord-derived neurons.…”
Section: Discussionmentioning
confidence: 99%
“…There has been increasing attention on the molecular mechanisms of NLRP3 in a number of diseases. Recent studies have reported significant protective effects resulting from suppression of NLRP3 inflammasome activation in liver fibrosis, systemic sclerosis, systemic lupus erythematosus, systemic sclerosis, diabetes, inflammasome-related eye disease, inflammatory bowel disease, rheumatoid arthritis, and CNS diseases (Zhou et al, 2016;Alegre et al, 2017;Rovira-Llopis et al, 2018;Shen et al, 2018;Yerramothu et al, 2018;Chen et al, 2019a). Meng et al (2019) demonstrated that PPARγ activation exerts an anti-inflammatory effect by suppressing NLRP3 inflammasome activation in spinal cord-derived neurons.…”
Section: Discussionmentioning
confidence: 99%
“…NEK7 has been found in NLRP3/ASC complexes: ASC complexes require NLRP3 complex formation and the interaction between NEK7 and NLRP3 is essential [ 83 ]. A recent study demonstrated the important role of NEK7 in regulating NLRP3 inflammasome, in fact, NEK7 knockdown significantly decreased caspase-1 activation, thus inhibiting pyroptosis and downstream inflammation following TBI [ 84 ]. However, the whole mechanism that explains how NEK7 modulates NLPRP3 inflammasome in neurons is still unknown.…”
Section: Nlrp3 Inflammasome Regulationmentioning
confidence: 99%
“…Subsequent studies indicate significant NLRP3 expression and inflammasome activity in intestinal epithelial cells that influence inflammatory bowel disease progression [25,26]. Sustained NLRP3 expression was observed in distressed neurons surrounding ischemic stroke [27] as well as in primary cortical neurons in an experimental traumatic brain injury (TBI) model [28]. Expression of the inflammasome family pattern recognition receptors NLRP1 and AIM2 has also been reported in neurons in mouse and rat models respectively [29,30].…”
Section: Introductionmentioning
confidence: 99%